What Is a “Substantial Burden” on Religion Under RFRA and the First Amendment? - Gabrielle M. Girgis (Washington University Law Review, 2020)
What is the meaning of a “substantial burden” on religion under the federal Religious Freedom Restoration Act (and its state-level equivalents)? This question is timelier than ever, as several pending cert petitions before the Supreme Court ask it to overturn the landmark decision that spurred RFRA’s enactment: Employment Division v. Smith, which held that exemptions for burdens on religion are not required from neutral and generally applicable laws. Whether or not the Court grants any of these cert petitions, judges will continue to need a clear and reliable method for identifying substantial burdens on religion. This Article considers several existing tests and proposes a new framework designed to remedy their shortcomings. Put simply, a court’s analysis of a substantial burden requires it to ask two questions: (1) What type of religious exercise does the law burden? And (2) what type of impact does the law have on that exercise? The Article develops answers to both questions, by specifying the kind of religious exercise that can be substantially burdened in the first place (what I’ll call obligation and substantial religious autonomy), and by sketching several types of substantial impact laws might have on religion (what I’ll call simply punitive, indirectly punitive, non-punitive, or preventive burdens). Only burdens that meet these two criteria together can properly be considered substantial. Taken together, these two prongs of the framework help us generate a taxonomy of at least eight different kinds of substantial burdens on religion. But a challenge remains: Would judicial application of this framework—particularly, would asking what type of religious exercise the law burdens— violate the Establishment Clause? In response, the Article clarifies the kinds of Establishment Clause concerns one might have about any judicial effort to interpret the substantiality of a burden on religion. Ultimately, it finds, the proposed framework can withstand all those concerns. Finally, the Article shows more precisely how the framework would help the Supreme Court decide a number of recent and potentially forthcoming cases involving substantial-burden claims.
Keywords: Religion Freedom Restoration Act; RFRA; Substantial burdens; First amendment; Free exercise; Establishment clause; Employment Division v. Smith